2007
DOI: 10.1002/cpp.541
|View full text |Cite
|
Sign up to set email alerts
|

Poor metacognition in Narcissistic and Avoidant Personality Disorders: four psychotherapy patients analysed using the Metacognition Assessment Scale

Abstract: Personality Disorders (PDs) are hypothesized to involve a decrement in the capacity to understand one's own thoughts and feelings. Patients may not, for example, recognize their own emotions or put together integrated representations of self with other. Some researchers have suggested that this deficit varies between the different PDs. However, empirical evidence that might confirm or disconfirm this hypothesis is scarce. The goal of the present research is to evaluate the metacognitive capacity in four partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 41 publications
2
60
1
6
Order By: Relevance
“…In support of this view, metacognitions have been found to be associated with a wide array of psychological and behavioural problems (for a full review, see Wells, ; Wells, 2013). Related research by Dimaggio and colleagues () and Lysaker and colleagues () has also highlighted the importance of an awareness of one's own mental state and the ability to recognize the mental states of others in personality disorder. This is of particular relevance in studying metacognition in CFS because of the high prevalence of personality disorders found in CFS (e.g., Henderson & Tannock, ).…”
Section: Introductionmentioning
confidence: 97%
“…In support of this view, metacognitions have been found to be associated with a wide array of psychological and behavioural problems (for a full review, see Wells, ; Wells, 2013). Related research by Dimaggio and colleagues () and Lysaker and colleagues () has also highlighted the importance of an awareness of one's own mental state and the ability to recognize the mental states of others in personality disorder. This is of particular relevance in studying metacognition in CFS because of the high prevalence of personality disorders found in CFS (e.g., Henderson & Tannock, ).…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the potential of psychotherapy to address metacognitive deficits, a broad literature has suggested that psychotherapy can promote metacognitive capacity (sometimes referred to as mentalizing) in persons with personality disorders, depression, and anxiety (Bateman & Fonagy, 2001; Dimaggio et al , 2007; Karlsson & Kermott, 2006). With regard to schizophrenia, case studies have provided some evidence that metacognitive capacity may be addressed in individual psychotherapy and that changes in metacognition may lead to improvements in function (Buck & Lysaker, 2009; Lysaker, Buck, & Ringer, 2007; Lysaker, Davis, et al , 2005; Salvatore et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We endorse here elements from dialogical self theory (Hermans, 2002;Lysaker & Lysaker, 2002), which offers a model of how parts of the self engage in a constant flow of conversation, and from metacognitive theory (Dimaggio & Lysaker, 2010;-and related concepts such as a mentalization, theory of mind, or social cognition-which offer models of how persons with significant pathology may lack the set of psychological skills needed to recognize and reason about their own minds.…”
mentioning
confidence: 97%